Pedagogic Education in Russia and Its Potential Development Strategy - V. I. Zagvyazinsky; L. D. Plotnikov; L. M. Volosnikova (Образование и наука)
The paper reflects on the current state and development trends of higher pedagogic education in Russia, and considers the possibility of either renewal or liquidation of education in question. The authors maintain that teachers’ training system should be preserved, and emphasize the need for the proper strategy development combining both the best educational traditions and leading concepts and technologies. It is recommended to modify all the modern educational establishments – colleges, pedagogical institutes and pedagogical universities. The special emphasis should be on teachers’ training at autonomous pedagogical institutions within the university complexes, and educational standards and curricula developments. In authors’ opinion the classical education effectively combines all the aspects of teachers’ training – the research capability, education fundamentality and cultural awareness. The experience of teaches’ training in Tumen State University is revealed.